2018
DOI: 10.1053/j.gastro.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B-Mediated Activation of Trypsinogen in Endocytosing Macrophages Increases Severity of Pancreatitis in Mice

Abstract: Studying pancreatitis in mice, we found activation of digestive proteases to occur not only in acinar cells but also in macrophages that infiltrate pancreatic tissue. Activation of the proteases in macrophage occurs during endocytosis of zymogen-containing vesicles, and depends on pH and CTSB. This process involves macrophage activation via NF-κB-translocation, and contributes to systemic inflammation and severity of pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
217
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(234 citation statements)
references
References 58 publications
3
217
0
4
Order By: Relevance
“…Injured acinar cells initiate inflammatory responses by releasing proinflammatory cytokines, digestive enzymes, and nuclear damage-associated molecular patterns molecules, which attract and activate immune cell to exacerbate tissue injury 20, 21 . It has been demonstrated that pancreatic acinar cells undergo necrosis when exposed to supraphysiological cerulein in vitro 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Injured acinar cells initiate inflammatory responses by releasing proinflammatory cytokines, digestive enzymes, and nuclear damage-associated molecular patterns molecules, which attract and activate immune cell to exacerbate tissue injury 20, 21 . It has been demonstrated that pancreatic acinar cells undergo necrosis when exposed to supraphysiological cerulein in vitro 22 .…”
Section: Resultsmentioning
confidence: 99%
“…To mimic pancreatitis caused by pancreatic duct obstruction (e.g., gallstones), we used a mouse model of pancreatitis by ligating the tail region of the pancreas for 24 hours (83). In this model, we observed that TRPV4-KO mice were substantially protected.…”
Section: Discussionmentioning
confidence: 99%
“…Activated pro-inflammatory macrophages (M1) release copious amounts of cytokines, including interleukin 6 (IL6), IL12, IL1β and tumour necrosis factor alpha (TNFα), early in the inflammatory response and in AP make a significant contribution to the systemic inflammatory response syndrome linked to organ dysfunction and death [12]. Recently extra-acinar protease activation within macrophages during endocytosis of zymogen-containing vesicles has been shown to participate in the systemic inflammatory response and determine AP severity [39]. In our study, the PMA-induced ECAR response of AP patient monocytes was also greater than those of healthy volunteers, indicating an enhanced glycolytic component of ATP production during the respiratory burst with prioritisation of cellular oxygen to generate free radicals.…”
Section: Discussionmentioning
confidence: 99%